2015
DOI: 10.5539/jas.v7n10p101
|View full text |Cite
|
Sign up to set email alerts
|

“Live Tilapia”: Diversifying Livelihoods for Rural Communities in México

Abstract: This study documents the socioeconomic impact of an innovation based on the marketing of live aquaculture products in rural communities as the Live Tilapia Points of Sales (LTPOS). A case study research conducted where the participatory strategy of "Simultaneous Production Growth Groups" (SPGG) was applied for technology innovation, which includes technology modules, organizational strategy and operational management. The results were evaluated socially and economically. In 14 months, 3531.50 kg of live tilapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Building partnerships between the links is necessary for quality and quantity, and to maintain product quality during its transit through the chain to meet the regional market (Table 4). Based on the performance of "Point of Sales of Live Tilapia" as a marketing strategy to increase the competitiveness of the agrifood-chain in the Sotavento region of the state of Veracruz (Lango-Reynoso et al, 2015), the system is not articulated. Thus, the system cannot be promoted and managed by its organization through cooperative agreements among the actors to coordinate their production resources and generate cognitive capacities and learning, which differs from other competing systems; strategies needed to maintain and grow the participating companies (Nooteboom, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building partnerships between the links is necessary for quality and quantity, and to maintain product quality during its transit through the chain to meet the regional market (Table 4). Based on the performance of "Point of Sales of Live Tilapia" as a marketing strategy to increase the competitiveness of the agrifood-chain in the Sotavento region of the state of Veracruz (Lango-Reynoso et al, 2015), the system is not articulated. Thus, the system cannot be promoted and managed by its organization through cooperative agreements among the actors to coordinate their production resources and generate cognitive capacities and learning, which differs from other competing systems; strategies needed to maintain and grow the participating companies (Nooteboom, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As a business strategy to increase the competitiveness of the Tilapia Agrifood-Chain based on its own resources and the nature of the territory, a network marketing of live tilapia was established at specified points of sale (Lango-Reynoso et al, 2015). Building partnerships between the links is necessary for quality and quantity, and to maintain product quality during its transit through the chain to meet the regional market (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of restaurants, the aquaculturist is closing the marketing links, bringing his transformed product directly to consumers and this activity should be replicated, to strengthen the incomes of those who do not yet practice it. This approach is defended by [82][83][84] in Veracruz, who developed the "live tilapia concept", bringing fresh and live product to the consumer. In addition, both [85,86] concluded that aquaculture favored the diversification of economic activities; a positive aspect for the development of the Mexican rural sector that currently prevails.…”
Section: Socioeconomic Informationmentioning
confidence: 99%